Studies on Seljuk History on the 100th Anniversary of Republic of Turkey - Muharrem Kesik (Tarih Dergisi)
Seljuk history occupies a significant place in Turkish history. Despite its importance, research and efforts to promote and study this field started relatively recently. One of the greatest challenges in this field was the historical inability to train a sufficient number of qualified experts on Seljuk history. However, in recent years, the growing interest in Seljuk history has led to a significant increase in the number of books published in the field. In addition, activities such as seminars, symposiums, exhibitions, projects, archaeological excavations, documentaries, feature films, and television series on Seljuk history have also been multiplied. Even though Seljuk history studies could not reach the desired level by the 100th anniversary of the establishment of the Republic of Turkey, it has nevertheless made a very significant breakthrough in the past 15–20 years. In this study, the details and lists of activities related to the subject will be included.